CRISPR-based m6A modification and its potential applications in telomerase regulation - Yi, Mingliang; Wang, Mingyue; Xu, Yongjie; Cao, Zhikun; Ling, Yinghui; Zhang, Zijun; Cao, Hongguo (Frontiers in Cell and Developmental Biology, 2023)
Telomerase determines cell lifespan by controlling chromosome stability and cell viability, m 6 A epigenetic modification plays an important role in the regulation of telomerase activity. Using CRISPR epigenome editing to analyze specific m 6 A modification sites in telomerase will provide an important tool for analyzing the molecular mechanism of m 6 A modification regulating telomerase activity. In this review, we clarified the relevant applications of CRISPR system, paid special attention to the regulation of m 6 A modification in stem cells and cancer cells based on CRISPR system, emphasized the regulation of m 6 A modification on telomerase activity, pointed out that m 6 A modification sites regulate telomerase activity, and discussed strategies based on telomerase activity and disease treatment, which are helpful to promote the research of anti-aging and tumor related diseases.